Field research 2011 - Kansas State University. Agricultural Experiment Station; Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2011)
Includes research reports from these locations: East Central Kansas Experiment Field, Harvey Country Experiment Field, Kansas River Valley Experiment Field, and Northwest Kansas Agricultural Research Centers.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1048; Kansas Agricultural Experiment Station contribution; no. 11-223-S; Kansas; Agriculture; Crops; Weed control; Disease control; Irrigation; Fertilizer